MASS ANALYSIS OF CESIUM ION INDUCED FRAGMENTATION OF C60 - Zeeshan, S.; Yamin, S.; Javeed, S.; Yaqub, K.; Ashraf, A.; Janjua, S. A.; Awais, A. (The Nucleus, 2011)
Results of Cs ion induced C60 fragmentation in source of negative ions by cesium sputtering (SNICS) from 5 MeV Tandem accelerator are presented. The mass analysis was performed from bending magnet. Mass spectra of C60 fragments are compared with that of graphite under similar conditions. Yield of carbon clusters for both cases is plotted for Cs ion energy range of 2-5 keV. It is observed that heavier clusters appear in the case of C60. Intensity of C2 is much higher in comparison with other clusters for both C60 and graphite due to difference in their bond energies. Prominence of C2 yield confirms formation mechanism of C60 by addition of C2 route.